Who Needs Big Health Sector Reforms Anyway? : Seychelles' Road to UHC Provides Lessons for Sub-Saharan Africa and Island Nations - Workie, Netsanet Walelign (Taylor and Francis, 2019)
The road to universal health coverage (UHC) needs not be driven by big reforms that include the initiation of health insurance, provider–funder separation, results-based financing, or other large health sector reforms advocated in many countries in sub-Saharan Africa and elsewhere. The Seychelles experience, documented through a series of analytical products like public expenditure reviews and supporting surveys with assistance from the World Bank and World Health Organization (WHO), shows an alternative, more incremental reform road to UHC, with important lessons to the region and other small-population or island nations. Done well, in some countries, a basic supply-side funded, publicly owned and operated, and integrated health system can produce excellent health outcomes in a cost-effective and sustainable way. The article traces some of the factors that facilitated this success in the Seychelles, including high political commitment, strong voice and a downward accountability culture, strong public health functions, and an impressive investment in primary health care. These factors help explain past successes and also provide a good basis for adaptation of health systems to dramatic shifts in the epidemiological and demographic transitions, disease outbreaks, and rising public expectation and demand for high quality of care. Once again, how the Seychelles responds can show the way for other countries in the region and elsewhere regardless of the types of reforms countries engage in.